Simple encoding method of phase-only hologram for low crosstalk full-color multi-plane holographic projection. (December 2021) - Pang, Yingfei; Cao, Axiu; Wang, Jiazhou; Pang, Hui; Deng, Qiling
Highlights: Simple encoding method of generating a phase-only hologram (POH) for low crosstalk full-color multi-plane holographic projection. Encoding algorithm based on the analytical formula with no iteration. Colorful reconstructed images with low crosstalk carried out by numerical simulations and optical experiments. Abstract: Full-color holographic three-dimensional (3D) projection technology is an important research direction in the field of holographic 3D display, which is committed to providing the viewer with 3D impression and color experience. A simple encoding method of generating a phase-only hologram (POH) for low crosstalk full-color multi-plane holographic projection is proposed. Multiple two-dimensional (2D) slice images of a full-color 3D object can be reconstructed by a single composite hologram generated by the proposed encoding algorithm based on the analytical formula with no iteration. Numerical simulations and optical experiments show that colorful reconstructed images with low crosstalk are achieved successfully. The number of the projection planes can be dozens, as long as the size of hologram is increased and the intervals between different planes are designed reasonably. Meanwhile, the encoding method is realized with no iterative optimization required, which will speed up the calculation of the POH and the size of the system will be small and compact. It is expected to be used for realizing full-color 3D holographic display in future.